Roles of plasminogen activator inhibitor-1 and -2, and receptor of urokinase-type plasminogen activator (u-PA) in tumor growth and metastasis - Takada, A.; Takada, Y. (Hämostaseologie, 2000)
Aim: Roles of urokinase-type plasminogen activator (u-PA) and its receptor (u-PAR), and its inhibitors (PAI-1 and PAI-2) in colon and breast cancer growth and metastasis were investigated. Methods: Antigen levels of u-PA, u-PAR, PAI-1 and PAI-2 were measured in lung tumor sites and its normal neighboring tissues and metastasis sites. mRNA of these factors was measured by Northern blotting and localization of these factors was measured by in situ hybridization. Results: Antigen levels of u-PA, u-PAR, PAI-1 and PAI-2 were higher in both lung and colon cancer tissues than in normal tissues. mRNAs of u-PA, u-PAR, PAI-1 and PAI-2 were all detected in lung cancer tissues. The amounts of u-PA and PAI-2 mRNA were significantly higher in lung cancer tissues than in normal lung tissues. Both u-PAR and PAI-1 levels were significantly higher in large than in small colon tumors. Higher levels of u-PAR were found an independent prognostic value by multivariate analysis. Conclusion: Antigens and mRNAs of u-PA, u-PAR, PAIs were found in tumor tissues.
Keywords: Cancer; metastasis; u-PA; u-PAR; PAI-1; PAI-2